Inventions and Production - Graue, Erwin (The Review of Economics and Statistics, 1943)
The data on inventions, which are used here, are based exclusively on patents issued for technological contrivance, and they do not include grants by the United States Patent Office for trade marks, labels, prints, and designs. These items are excluded because they are largely extraneous to the tangible factors of mechanical adaptation that influence processes of production. Chart i reveals clearly the tendency for inventions and production, during the entire period from I863 to I939, to move along one general course. Of particular interest, however, is the behavior of these series over shorter periods: from I863 to I894; from I895 to I9I5; and from I9I6 to I939. In the first period, following the Civil War, the yearly fluctuations were of considerable amplitude, and each series displayed an independent upward movement. During the early years of the period, the divergence between the two series was fairly wide, but a decrease in this divergence began around I878, when the